2023
DOI: 10.1186/s12912-023-01497-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an online training program for improving nurses’ competencies in disaster risk management

Jamileh Farokhzadian,
Hojjat Farahmandnia,
Asghar Tavan
et al.

Abstract: Background Nurses’ incompetency in disaster risk management can have many negative consequences during disasters, so it is important to prepare nurses and improve their competencies in disaster risk management. This study was conducted with the aim of investigating the effectiveness of an online training program to improve competencies in disaster risk management. Method This interventional study was conducted on nurses working in a specialized tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…From the appraised studies, implementing leadership enhancement programs such as The Nurse Manager Development Program, Train-the-Trainer Program [29] and Nurse online training kit Farokhzadian [12] should outline the essential knowledge, skills and competencies a nurse leader should exercise and provide a guide for further improvement of the hospital setting. Equally worrying is that some hospitals have limited staff nursing expertise, experience and a bachelor's or a master's degree.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From the appraised studies, implementing leadership enhancement programs such as The Nurse Manager Development Program, Train-the-Trainer Program [29] and Nurse online training kit Farokhzadian [12] should outline the essential knowledge, skills and competencies a nurse leader should exercise and provide a guide for further improvement of the hospital setting. Equally worrying is that some hospitals have limited staff nursing expertise, experience and a bachelor's or a master's degree.…”
Section: Discussionmentioning
confidence: 99%
“…The studies pointed to the importance of nurse managerial competence in running daily nursing activities [11][12][13][14]. In the first study, Goktepe et al (2018) [11] found that nurse managers aged ≥ 35 years, with ≥ 15 years of experience in the health profession and over 10 years in-service in the present hospital facility had higher pre-test scores compared to other nurses.…”
Section: Nurse Managerial Competencies and Professional Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…By participating in educational programs and disaster 2 of 13 response exercises, nurses can acquire expertise and competence in managing catastrophic situations [11]. The use of simulated drills and exercises, complemented by regular assessments and including practical drills, enhances nurses' understanding of essential disaster management skills [12]. A solid understanding of the core principles of crisis management is crucial for nurses to perform effectively during catastrophic events [11,13,14].…”
Section: Introductionmentioning
confidence: 99%